Pengembangan Masyarakat dan Manajemen Dakwah - Musholi, Musholi (Tasamuh: Jurnal Studi Islam, 2017)
Propaganda management is the ability to identify problems and then plan appropriate, organize and coordinate the executors of propaganda in certain units. Thus, management of the mission is a process of utilizing the resources (human and natural) and made to realize the values of Islam as a common goal. The management of the mission is a systematic and coordinated arrangement in proselytizing activity or activity that starts from before the execution until the end of the implementation of propaganda. While development managerial is a part of managerial behavior. It’s included training which is used as a means to improve one’s skills and facilitate adjustment to work and career advancement. Someone involved in an organization, not always immediately able to master and has the skills in the management of the organization, so that training and cadre member of the organization is absolutely necessary to prepare qualified resources. Term development of the translation of a term development translates into two terms, namely: the first term to the idea or natural thought. The second term is defined as a respect. The idea of change and the creation the ability to act in a world are full of struggle and competition. Both meanings are closely related with each other. With forward thinking will create the desire to raise the idea in changing circumstances into thriving communities